If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 12 + -5x + -9 = 0 Reorder the terms: 12 + -9 + 8x + -5x = 0 Combine like terms: 12 + -9 = 3 3 + 8x + -5x = 0 Combine like terms: 8x + -5x = 3x 3 + 3x = 0 Solving 3 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = 0 + -3 3x = 0 + -3 Combine like terms: 0 + -3 = -3 3x = -3 Divide each side by '3'. x = -1 Simplifying x = -1
| 8x+2=8(x+4) | | 5/2x=15/12 | | 3x+11-6x=15-14x+11x-4 | | 3(2x+1)-5=6x-2 | | 0.06(y-9)+0.04y=0.08y-0.01(60) | | 1/3+10u=y/v | | 6=-2910n+7 | | 8-(3+7)=23 | | 0.4x+56000(0.2+x)=1400 | | B=xm+m | | 2y^3+2+6y^2+6y= | | 4(3+5x)=47 | | 5p-13=8p+4 | | 5x-3+3(2x+2)=-3(x+3) | | tn=5n+7 | | 7x+8x=13x | | 6x+7-2x=19 | | 5x+7(x-1)=-3 | | 2y-6=2x | | 5a+10=3a+10 | | x+(x*0.07)=35.19 | | 14(t-6)+4t=6(3t+5)-8 | | (6x-6)-(13x+8)= | | 3x-5(x-3)=16-4x | | x+(x*0.07)=28.25 | | -13x=234 | | -(4y+4)-(-3y-8)=-2 | | 1/4+3/8x=3/4 | | 3.5+0.75x=17.00 | | 10x+5/2y=20 | | 2x-1-.5-6x-x= | | x+(x*0.07)=131.8 |